2003
DOI: 10.1046/j.1365-201x.2003.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of jump training on passive mechanical stress and stiffness in rabbit skeletal muscle: role of collagen

Abstract: These results suggest that jump training can increase muscle capabilities of strength and stiffness in fast-twitch mixed muscles with pennate architecture (EDL, RF). This increase is essentially mediated by a rise in cross-linked collagen fraction, coupled with a relative decrease in soluble collagen. The collagen covalent cross-links improve resistance and stability in force transmission processes during stretching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 37 publications
7
55
2
3
Order By: Relevance
“…The greater redness index of meat in rabbits reared in large pen compared to those reared in small pen and caged rabbits can be attributed to enhance of locomotory behaviour. Indeed, it has been shown previously that physical activity increased oxidative energy metabolism and enhanced the proportion of type I and of type IIA fibres rich in mitochondria and myoglobin when compared to sedentary animals (Ducomps et al, 2003;Gondret et al, 2009). As observed in the PCA plot (Figure 1) in our experiment, increased redness was related to low ultimate pH in LL and in BF.…”
Section: Discussionsupporting
confidence: 68%
“…The greater redness index of meat in rabbits reared in large pen compared to those reared in small pen and caged rabbits can be attributed to enhance of locomotory behaviour. Indeed, it has been shown previously that physical activity increased oxidative energy metabolism and enhanced the proportion of type I and of type IIA fibres rich in mitochondria and myoglobin when compared to sedentary animals (Ducomps et al, 2003;Gondret et al, 2009). As observed in the PCA plot (Figure 1) in our experiment, increased redness was related to low ultimate pH in LL and in BF.…”
Section: Discussionsupporting
confidence: 68%
“…MacDougall et al 21) have shown that the proportion of intramuscular connective tissue in the biceps brachii did not differ between bodybuilders and control subjects. In contrast, Ducompus et al 9) have shown in rabbits that highintensity exercise training induced a significant increase in intramuscular collagen concentration in the extensor digitorum longus and rectus femoris, but not in the semimembranosus proprius. Taken together, it is likely that the effects of training and its associated muscle CSA on the proportion of connective tissue are dependent on the muscles examined.…”
Section: Discussionmentioning
confidence: 93%
“…Such compositional variabilities can modulate the passive material properties of muscle. Additionally, a previous study has shown in rabbits that high-intensity exercise training induced a significant increase in intramuscular collagen concentration 9) , leading to an increase in the passive material properties of a muscle, since the passive material properties of a muscle can be influenced by the collagenous connective tissues within the muscle 10,11) . Thus, it is reasonable to assume that the passive material properties of muscle differ among individuals, and that muscle with greater CSA (i.e., hypertrophied muscle) is stiffer.…”
Section: Introductionmentioning
confidence: 99%
“…The EMD changes during training are mainly attributed to changes in the tendon structure, but it should be noted that tendon stiffness is always increased during any physical activity, both during endurance (Buchanan and Marsh 2001) and isometric training (Kubo et al 2000. Furthermore, EMD changes correlate very closely with muscle MTC and especially with the active SEC fraction during training (Pousson et al 1991;Ducomps et al 2003, Malisoux et al 2006.…”
Section: Influence Of Simulated Microgravity On Mechanical Propertiesmentioning
confidence: 99%
“…Endurance training resulted in an increase in the SEC stiffness in the soleus muscle of rats, associated with an increase in type I fibres (Goubel and Marini 1987). Both jump and endurance training also appear to increase both collagen concentration (Kovanen et al 1980;Ducomps et al 2003) and muscle passive stiffness. The soleus rat muscles submitted to plyometric training had more fast twitch fibres and a lower SEC stiffness than controls (Watt et al 1982;Pousson et al 1991;Almeida-Silveira et al 1994).…”
Section: Influence Of Simulated Microgravity On Mechanical Propertiesmentioning
confidence: 99%